The Administration and the information provided in extraordinary situations related to health. The Ebola virus crisis - Ibáñez Peiró, Ángel (Revista Española de Comunicación en Salud, 2019)
In Spain, the National Health System has a high level of excellence. But this good reputation may sometimes be marred as a result of an inadequate managing of the public function of informing by both, its components and the Administration. This essay is based on a research of this author about managing Public Information by the State to face extraordinary situations related to health, analyzing the crisis caused by the Evola virus in Spain in 2014. The point of view on which this study is made is based on the objectivity of the empiric data, the regulations about communication and the use of technical parameters in the valoration of media reports. In this context these parameters are analyzed: the acting and responsibility of media professionals, the information sources, and some ethycal, deontological and legal aspects that must be taken into account by those concerned with giving an answer to these kind of situations, specially the professionals of public health and political authorities.